POLA KEMITRAAN PENTAHELIX UNTUK PENINGKATAN KOMPETENSI PEMASARAN PELAKU USAHA MIKRO KECIL MENENGAH : (Program Kolaborasi Solo Technopark Bersama Bukalapak) - Sholihah, Amalia Putri; Hendrawijaya, Arief Tukiman; Hilmi, Muhammad Irfan (IKIP Siliwangi, 2024)
Partnership is a collaboration between two or more partner that jointly benefit each other to build joint collaboration in activity program using the pentahelix model partnership. Pentahelix which consist of 5 stakeholders GBCAM (Government, Business, Community, Academy, Media). The collaboration partner between Solo Technopark and Bukalapak is signed with a cooperation agreement and MoU (memorandum of Understanding) that is legally valid and exsiting SOPs. Activities are conducted in the form of workshops and webinar. This activity was implemented because many business actors did not really understand about marketing. That way Solo Technopark and Bukalapak want to make MSME actors more advanced and able to improve human resources through workshops and webinar. Presented material in the form of 4P’s marketing mix consisting of product, process, place, and promotion. With the aim that thet are able to absorb the material presented and can improve marketing competencies to compete with the current market. This research uses descriptive research with a qualitative approach to obtain in-depth information and based on facts in the field during this research. The result showed that the partnership with the pentahelix model can be carries out well. Workshops and webinar activities are able to provide MSME actors with increased marketing competence in the form of knowledge and skills.